What Drives International Performance? Insights from Computer-Related Service Firms - Etemad-Sajadi, Reza (2012)
The aim of this paper is to understand the drivers of international performance for service firms. Qualitative interviews and a literature review are used to build the model which is tested empirically on computer-related (CR) service firms using structural equation modeling (SEM). Results show that standardized services and services requiring limited face-to-face contact positively influence international performance. In addition, joint venture and establishment abroad are the two most effective modes of entry. Finally, firm size and international experience are also significant drivers of international performance. As a practical implication, the research suggests that firms with limited capabilities should prefer to export standardized services requiring limited face-to-face contact.